Creative Multimodal Learning Environments and Blended Interaction for Problem-Based Activity in HCI Education - Ioannou, Andri; Vasiliou, Christina; Zaphiris, Panayiotis; Arh, Anja; Klobučar, Tomaž; Pipan, Matija (My University, 2015)
This exploratory case study aims to examine how students benefit from a multimodal learning environment while they engage in collaborative problem-based activity in a Human Computer Interaction (HCI) university course. For 12 weeks, 30 students, in groups of 5-7 each, participated in weekly face-to-face meetings and online interactions. Students’ selfreports and tutor’ observations showed that overall students benefited from the multimodal learning environment while they engaged in blended interactions across physical and digital tools and across collocated and networked learning spaces. With respect to tool use, it was found that the downward pointing projector and Facebook were used in all phases of problem based activity, while portable devices for record keeping were mainly used in progress evaluation and reflection phases.
Keywords: Multimodal learning; Learning environment; Blended interaction; Technology enhanced learning; Facebook; Smart devices; Problem-based learning; Technology adoption; CHI education